Effect of multiple water resources in a flexible-schedule batch water network. (1st July 2016) - Chaturvedi, Nitin Dutt; Manan, Zainuddin Abdul; Wan Alwi, Sharifah Rafidah; Bandyopadhyay, Santanu
Abstract: The operating cost of a water network can be significantly reduced via utilization of multiple water resources. In a batch process, scheduling plays a vital role towards resource conservation. This work analyzes the effect of multiple water resources on a batch water network schedule. It is proven that, in minimizing the operating cost of a batch water network, the exact schedule that leads to the minimum operating cost for multiple water resources also applies to systems involving a single water resource. This leads to a vital theorem that, once the optimum schedule for a single resource leading to the minimum operating cost is obtained, the same schedule can be applied for problems involving multiple resources. The findings in this paper have provided a simplified conceptual approach of dealing with scheduling problems with multiple water resources. Applicability of the proposed theorem is demonstrated via an illustrative example. Highlights: A conceptual approach to deal with scheduling problems with multiple water resources. A-theorem to minimize operating cost for multiple water resources. The theorem is proven using rigorous mathematical arguments. The schedule that minimizes operating cost applicable for single and multiple resources.